Factors influencing the experience of the terminal phase and the grieving process: the primary caregiver’s perspective - Pazes, Maria Catarina Estevens (2016)
Theoretical framework: The experience of the terminal phase and death by patients and caregivers is influenced by multiple factors. This study aimed at understanding this experience from the primary caregiver’s perspective. Objectives: To describe the factors that, from the primary caregiver’s perspective, influenced the experience of disease in the terminal phase and mourning for the death of a close person; To understand the influence of nurses’ conduct on the experience of disease in the terminal phase and mourning for the death of a close person from the primary caregiver’s perspective. Methodology: Qualitative descriptive exploratory study. Results: The following factors were valued: To Assume the Caregiver’s Role, To allow for the end-of-life/terminal phase to take place at home/near the family and Process of Care. Regarding the nurses’ conduct, the knowledge, communication and relationship established by nurses were also valued. Conclusion: In addition to expanding the implementation of specific palliative care teams, the acquisition and development of basic skills in this area by most health care professionals is essential.